“Está no sangue”: etnografia sobre a perspectiva hereditária das mucopolissacaridoses no Cariri paraibano - Marques, Heytor de Queiroz (2020)
This work intends to understand the conception of inheritance and heredity from families affected by mucopolysaccharidosis, a rare genetic disease of high prevalence in Cariri Paraibano. Genetically, the disease is attributed to consanguineous marriage or marriage between cousins, with a higher concentration in the region where the research was carried out. The interest arose from questionings that it would be an "inherited" disease - that is, having a strong bond with kinship and how this bond interferes in the family organization. The objectives were: to understand the perception of genetic and social inheritance/heredity of families affected by Mucopolysaccharidosis in Cariri Paraibano. As for the specific objectives: to verify the relationships between family members and the patient after the positive diagnosis; to identify the family perceptions about the disease and its hereditary character; to identify the repercussions on the personal and family trajectory from the disease and its hereditary character; to analyze the daily changes in the lives of the family members of those affected. Methodologically, the field work was carried out in two expeditions, to talk to the families and people with mucopolysaccharidosis. The first expedition was carried out together with my advisor and we visited 11 cities scattered throughout the Cariri region. In the second expedition, I visited two cities, Serra Branca and Taperoá, due to the large number of families affected and with the objective of deepening the investigation started by getting to know how the family constitution happened, by assembling genealogies of the families, it was also possible to meet new interlocutors who were not identified in the first trip to the field. In total, 16 families were visited and semi-structured interviews were carried out, 13 of them in the first expedition and 3 new families in the second, making it possible to meet members of these families. The interviews varied according to the situation of each family, so that sometimes only the fathers and/or mothers were the agents of dialogue when the children were children, and when they were already adults they spoke for themselves, but with the company of some other family member. Among the families, the significant aspect to be pointed out concerns the value of blood attributed to the passing on of the disease, not to kinship, characterized by having the "same blood". Those families that took kinship as a reference was in the sense that: "it is only family when the same blood runs in the veins," and that blood in the veins that shares the risk of illness in the family. The inheritance could also be manifested from the understanding of the heredogram performed by the geneticist, which would be an instrument to point out the kinship relationship, but for the interlocutors it made no difference, because the kinship was built from a social normative, in which it would be defined by a proximity in relationships. Another way of understanding kinship would be with a historical notion in the territory in which the family originally settled and there they were putting down roots and little "mixing", thus preserving the surname and the genetic material in the same territory that started as farms and became a city. Finalizing the data presentation, the inheritance of risk and family reproduction emerges as a theme well understood by one of the interlocutors in order to understand and help problematize what it would be like to live with the risk of developing a rare genetic disease, the mucopolysaccharidoses, bringing a contrast of this interlocutor with the other participants in the group who did not question or did not place the risk as a fundamental point for the construction of their families. The mucopolysaccharidoses are understood by the interlocutors as inheritances that can arise from blood relationships, but these relationships are rarely admitted, because social rules prevail over genetic knowledge. In addition, inheritance can be understood from the territory that makes a direct connection with the names of the families and their residence in places that became cities. Finally, inheritance can also be understood as a risk in family construction, since it can affect the possibility of having a child with mucopolysaccharidosis or not, and this condition entails several changes and brings several dilemmas about family formation.